PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR SISWA - Rangkuti, Ahmad Nizar (Institut Agama Islam Negeri Padangsidimpuan, 2018)
The emergence of this research is based on the lack of mathematical skills of students, especially at the primary / MI. Lack of ability is one of them triggered by the selection and use of learning approaches that are less varied. This research is a quantitative research in the form of experiments. Data collection techniques used instrument of observation, interviews and tests. Analysis of data such as observation data and interviews conducted with descriptive analysis and quantitative data were analyzed using statistical formulas in the form of t-test with SPSS version 17. The results showed there are significant PMR approach to the learning outcomes of students in Class VA MIN 1 Padangsidimpuan.